ANALISIS PERTUMBUHAN DAN HASIL TANAMAN JAGUNG MANIS (Zea mays-saccharata Sturt), PADA JUMLAH BENIH DAN DOSIS PUPUK MAJEMUK - Akbar Bimantoro; Maria Theresia, Darini; Sri, Widata (JURNAL ILMIAH AGROUST, 2024)
This research aims to obtain the right number of seeds per planting hole and the right dose of NPK fertilizer so that it can increase the growth and yield of sweet corn plants, and test whether there is an interaction between the number of seeds per planting hole and the dose of NPK fertilizer which can increase plant growth and yield. sweet corn. The research was carried out on the land of the Pelangi Mendungan Adult Farmers Group, Giwangan, Umbulharjo, Yogyakarta and at the Integrated Laboratory, Sarjanawiyata Tamansiswa University Yogyakarta. The research will start from June – December 2022, arranged in a Complete Randomized Block Design (RAKL) with 4 replications. The first factor is the number of seeds (D) one and two seeds per planting hole. The second factor is the dose of NPK (N) fertilizer (100, 150, and 200) kg/ha. The research results were analyzed using variance at the 5% level, then continued with the Duncan'S Multiple Range Test (DMRT) at the a = 5% level. There was no interaction between the number of seeds per planting hole and the treatment dose of NPK fertilizer on all growth and yield variables. The number of seeds per planting hole influence the analysis of growth and yield of cob weight, the number of 1 seed per planting hole increases the weight per husked ear, while the number of 2 seeds per planting hole increases the wight of the ear per ha. The NPK fertilizer dose (100, 150, 200) kg/ha had no effect on growth and weight of sweet corn cobs per ha. Key words: sweet corn, weight of husked cobs, fresh weight per plant.